Manual de procesos en la Cooperativa de Ahorro y Crédito Agrícola Junín - Álvarez Mendoza, Erika Fernanda (2021)
This research consists of the development of a process manual for the Junín Agricultural Savings and Credit Cooperative whose objective is to design a process manual as a contribution to the continuous improvement of the activities of the personnel in it, A process manual is defined as that document that allows companies to organize their activities and optimize their resources in the best way, identifying those activities that do not generate value to the product in order to improve organizational quality. The research techniques used were the interview applied directly to the general manager of the Cooperative, Subsequently, a survey was carried out among the workers of the same and the application of an observation form, which allowed the identification of the processes that are developed in the Cooperative and thanks to this information it has been possible to design the process manual. For the design of this manual, other techniques were used, among which the process files were defined that allowed to collect information for the preparation of the same, the Visio tool was essential for the design of the process diagrams and the Ishikawa diagram that I provide the company to know the cause and effect of not having a process manual that allows them to define the activities carried out in the organization.